The Building Students' Character Through Religion Learning in Islamic School - Mufidatus Sholikhah (MODELING: Jurnal Program Studi PGMI, 2021)
This research aims to analyze the basic concept of building students' character through Islamic Religion Learning in Islamic School. The method used in this research was library research. The method used in collecting data are documentation and content analysis. The result shows that learning in Islamic School has a great impact to the daily life of the students. Building students' character through Islamic Religion Learning in Islamic School involves some subjects that become the scope of Islamic Religion Learning such as; Akidah Akhlak, Fiqih, Al-Quran Hadits, Sejarah Kebudayaan Islam. Those are directed to the three types of intelligences namely intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ).